Causes of death through verbal autopsy: findings from a sub-study of single dose oral cholera vaccination in urban Dhaka, Bangladesh - Md. Taufiqul Islam; Md. Mazharul I. Zion; Md. Arifuzzaman Khan; Zahid H. Khan; Faisal Ahmmed; Shamim Ahmed; Azimuddin Ahmed; Afroza Akter; Fahima Chowdhury; Amit Saha; Nirod C. Saha; Deok R. Kim; et al. (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Verbal autopsy can play a key crucial to identify significant causes of death in a developing country like Bangladesh where post-death pathological or forensic examination is not common. Single-dose Cholera Vaccination in Bangladesh (SCVB) was an individually randomized, placebo-controlled, double-blind study where verbal autopsy had been conducted for the participants who died within three months of receiving study agents This study aim was to determine the major causes of death through a verbal autopsy in a defined urban population. # Methods The trial was conducted in urban slums of Dhaka among persons aged one year and older. A census was carried out bi-annually in the study area (Mirpur) including collecting death information from every household. Screening data on death was matched with the vaccination database to confirm whether the participants received the investigational products (IP) or not. The trained physician conducted a verbal autopsy usually within 7 days of notification. # Results The screening period for verbal autopsy was from May 22 to July 18, 2014. Among 250 detected deaths, 99 received study agents (50 vaccines and 49 placeboes). The Verbal autopsy could not be completed for 10 deaths due to the unavailability of a next of kin respondent. Of the total of 240 verbal autopsies performed, 217 were in adults aged 18 years and above, 6 in 5-17 years of age, and rest were ≤ 5 years. The Most common causes of death were non-communicable diseases. 163 deaths occurred at home, 59 in a hospital and others died in different places. No significant difference in cause of death among vaccine and placebo group was found from this analysis. # Conclusions Verbal autopsies usefully identified probable causes of death in participants in an oral cholera vaccine trial. The findings highlight that in this urban slum, noncommunicable diseases account for most of deaths.